3.0k views
5 votes
Simplify (3x2 − 2) + (5x2 + 5x − 1). (2 points)

8x2 + 5x − 3

8x2 + 5x − 1

2x2 + 5x − 3

8x2 + 7x − 1

1 Answer

4 votes

Answer:

D

Explanation:

well the anser has to equal 9 if you solved the question correctly BUT the other questions have to equal 9 so the first one is like this

(3*2-2)+(5*2+5*-1)



= (6-2)+(5*2+5*-1)



= (4)+(5*2+5*-1)



= 4+(5*2+5*-1)



= 4+(10+5*-1)



= 4+(10+-5)



= 4+(10-5)



= 4+(5)



= 4+5



= 9

Now the answers A is not it because

8*2+5*-3



= 16+5*-3



= 16+-15



= 16-15



= 1

B isnt it because

8*2+5*-1



= 16+5*-1



= 16+-5



= 16-5



= 11

And C isnt it because

2*2+5*-3



= 4+5*-3



= 4+-15



= 4-15



= -11

So that leaves D and this is how it is correct

= 8*2+7*-1



= 16+7*-1



= 16+-7



= 16-7



= 9


Hope this helps! Sorry I took so long

User Nataliastanko
by
5.5k points